Parallel Processing Distributed-Memory Approach Influences on Performance of Multicomputer-Multicore Systems Using Single-Process Single-Thread - Dildar Masood Abdulqader; Subhi R. M. Zeebaree; Rizgar R. Zebari; Mohammed A. M.Sadeeq; Umed H. Jader; Mohammed Mahmood Delzy (Wasit Journal of Engineering Sciences)
Based on client/server architecture concepts, this research suggests a method for creating a multicomputer-multicore distributed memory system that can be implemented on distributed-shared memory systems. Both of number of the participated computers and number of existed processors for each of these computers, this research was depended with the specific design and its implementation. The suggested system has two primary phases: monitoring and managing the programmes that may be executed on multiple distributed-multi-core architectures with (2, 4, and 8) CPUs to perform a certain job. There might be a single client and unlimited servers in the network. The implementation phase relies on three separate scenarios covering most of the design space. The suggested system can determine the start time, duration, CPU use, kernel time, user time, waiting time, and end time for each server in the system. Single-Process Single-Thread (SPST) is considered a possible situation while developing User Programmes (UPs). The findings confirmed that more processing power (more servers and more processors on each server) increases the speed at which tasks can be solved. There was a 2.877-fold gain in task processing speed after considering three different possible SPST UPs situations. The C# programming language is used to create this system.